Inguinal hernia in hemodialysis versus peritoneal dialysis patients: a case-control study. Issue 1 (December 2016) - Banshodani, Masataka; Kawanishi, Hideki; Moriishi, Misaki; Shintaku, Sadanori; Hashimoto, Shinji; Nishihara, Masahiro
Abstract Background Inguinal hernia is common in dialysis patients, especially peritoneal dialysis (PD) patients; however, no previous reports have assessed the incidence, type, treatments, and risk factors of inguinal hernia in hemodialysis (HD) patients. We retrospectively evaluated the differences in these factors between HD and PD patients. Methods A total of 2287 HD and 410 PD patients treated between March 2006 and December 2013 were enrolled. The incidence, type (indirect, direct, or combined), and hernioplasty of inguinal hernia as well as demographic characteristics of HD and PD patients were compared. Results The incidence of inguinal hernia was lower in HD (0.7 %) than in PD patients (5.9 %) (P  < 0.001), and these incidences were higher among men (P  = 0.007 andP  < 0.001, respectively). Of the 16 HD and 24 PD patients with inguinal hernia, 14 and 21 (both 88 %) underwent hernioplasty. Among them, PD patients demonstrated a higher proportion of indirect hernia (91 %) than HD (47 %) patients (P  = 0.003). No recurrence was observed in either group. In a multivariate logistic regression model, PD and male sex were risk factors for inguinal hernia (bothP  < 0.001). Conclusions In this study, indirect inguinal hernia was more frequent in PD patients than in HD patients. Male sex and PD are risk factors for inguinal hernia in dialysis patients. Tension-free hernioplasty for inguinal hernia was effective in both HD and PD patients. Our findings can help inform clinicians when selecting the dialysis modality (HD or PD) prior to the initiation of dialysis therapy and guide clinical management practices for inguinal hernias in dialysis patients.